An Overview of Composite Pressure Vessels with Polymer Liner - zeinab rouzbehani; mehrnoush mohammadi (Baspārish, 2022)
Pressure vessels are one of the most widely used and high-risk equipment in various industries. Pressure vessels are divided into four types based on material and structure. Weakness in design, construction and production, service and especially incorrect choice of materials are the causes of pressure vessel failure. With the introduction of composites into the world of these vessels, many design weaknesses and their mechanical properties have been improved. By using high density polymers such as polyethylene, the weight of the pressure vessel is reduced. Type IV pressure vessels with the simultaneous use of composite structure and polymer liner are able to reduce weight by up to one-fifth and double the useful life compared to the type I of vessels. The advantages of the fourth type of pressure vessels are corrosion resistance, no fatigue in consecutive loads, lightness and portability, high operating pressure (700 bar) and lack of complexity of the production method, and their disadvantage is the high production cost due to the use of carbon fibers. These pressure vessels are used to store alternative fuels such as hydrogen and portable individual oxygen capsules. In this article, the pressure vessels types are briefly reviewed and the fourth type is compared with other types.